Pengaruh Terapi Murottal Surat Ar- Rahman Pada Ibu Dengan Postpartum Blues Di Tpmb Siti Alfiyah Dan Muarofah Kota Surabaya - Rahma Illahi, Gusti; Ma'rifah, Umi; Anifah, Fulatul (Indonesian Academia Health Sciences Journal, 2024)
Objective: To identify the effect of Ar-Rahman Murottal therapy on mothers with postpartum blues at TPMB Siti Alfiyah and Muarofah Surabaya Methods: This study used a Pre-experimental method with a One Group Pretest Posttest design approach with a total sample of 20 postpartum mothers. Sampling using consecutive sampling technique. The instrument used was the Edinburgh Post-natal Depression Scale questionnaire. Data analysis in this study used univariate analysis, bivariate analysis of cross tabulation. Resultsshowed that the magnitude of the decrease in the EDPS score of the incidence of postpartum blues before the Ar-Rahman murrotal therapy was an average of 12.65 and after the Ar-Rahman murrotal therapy was an average of 3.80 with a decrease of at least 1 and most 7. The results of the cross tabulation test showed a decrease in EPDS scores, which means that there is an effect of Ar-Rahman murrotal therapy on mothers with postpartum blues Conclusion: Ar-Rahman murrotal therapy is able to reduce the incidence of postpartum blues. Prevention of postpartum blues can be done in postpartum mothers early on with Ar Rahman Murottal therapy